The Place of ICTs in Libraries for Excellence in Teaching and Learning Process in Nigerian Tertiary Institutions - Olufunke, Adedeji Fausat (International Journal of Research in Interdisciplinary Studies, 2025)
Information and Communication Technologies (ICTs) have become integral to academic libraries worldwide, transforming how libraries support teaching and learning. Academic libraries serve as pivotal centers for knowledge acquisition, research, and learning support in tertiary institutions. The integration of ICTs into these libraries has revolutionized traditional library services, enabling faster access to information, digital resource management, and interactive learning environmentsIn Nigerian tertiary institutions, the adoption of ICTs in libraries has significantly enhanced access to information, resource sharing, and user engagement, thereby promoting excellence in education. This paper examines the role of ICTs in Nigerian academic libraries, their impact on teaching and learning, challenges faced, and recommendations for maximizing their benefits. Using a review of recent studies and case analyses, the paper highlights the critical place of ICTs in fostering an effective educational environment in Nigerian universities.